What are the indications and survivorship of tumor endoprosthetic reconstructions for patients with extremity metastatic bone disease?. Issue 7 (16th March 2023) - Kendal, Joseph K.; Hamad, Christopher D.; Abbott, Annalise G.; Greig, Danielle; Trikha, Rishi; Christ, Alexander B.; Wessel, Lauren E.; Puloski, Shannon K. T.; Monument, Michael J.; Bernthal, Nicholas M.
Abstract: Background and Objectives: Given advances in therapies, endoprosthetic reconstruction (EPR) in metastatic bone disease (MBD) may be increasingly indicated. The objectives were to review the indications, and implant and patient survivorship in patients undergoing EPR for MBD. Methods: A review of patients undergoing EPR for extremity MBD between 1992 and 2022 at two centers was performed. Surgical data, implant survival, patient survival, and implant failure modes were examined. Results: One hundred fifteen patients were included with a median follow‐up of 14.9 months (95% confidence interval [CI]: 9.2–19.3) and survival of 19.4 months (95% CI: 13.6–26.1). The most common diagnosis was renal cell carcinoma (34/115, 29.6%) and the most common location was proximal femur (43/115, 37.4%). Indications included: actualized fracture (58/115, 50.4%), impending fracture (30/115, 26.1%), and failed fixation (27/115, 23.5%). Implant failure was uncommon (10/115, 8.7%). Patients undergoing EPR for failed fixation were more likely to have renal or lung cancer ( p = 0.006). Conclusions: EPRs were performed most frequently for renal cell carcinoma and in patients with a relatively favorable survival. EPR was indicated for failed previous fixation in 23.5% of cases, emphasizing the importance of predictive survival modeling. EPR can be a reliable and durable surgical option for patients with MBD.